A Case Report on Ayurvedic Management of Lumbar Intervertebral Disc Protrusion with Sciatica - Nimisha George; Susmi P S; Keerthana R; Shitha Thomas (AYUSHDHARA, 2025)
Low back pain ranks first for disability and sixth for overall burden on world health with an annual approximate cost of 135 billion. It is a highly debilitated condition and one of the major causes of low back ache is sciatica. According to the severity it causes significant reduction in quality of life and ability to carry out day to day activities of those affected. The overuse of NSAIDs and analgesics by the public raises concerns, highlighting the need for effective, non-invasive alternatives like Ayurveda. This case study deals with the case of a 40-year-old married man who visited a tertiary care Ayurvedic hospital for low back pain radiating to bilateral lower limbs (left>right) since three months. He was a diagnosed case of sciatica with lumbar spine MRI findings of posterocentral intervertebral disc protrusion, anterior thecal sac indentation, narrowing of the bilateral lateral recess and moderate stenosis of the bilateral neural foramen. After undergoing Ayurvedic treatments, including Samana medicines and Panchakarma procedures, the patient experienced reduced pain and improved mobility, demonstrating the effectiveness of Ayurvedic management for sciatica.